-11=4(-2)-3

Simple and best practice solution for -11=4(-2)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11=4(-2)-3 equation:


Simplifying
-11 = 4(-2) + -3

Multiply 4 * -2
-11 = -8 + -3

Combine like terms: -8 + -3 = -11
-11 = -11

Add '11' to each side of the equation.
-11 + 11 = -11 + 11

Combine like terms: -11 + 11 = 0
0 = -11 + 11

Combine like terms: -11 + 11 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 20+43=17+x | | -28+0.3x=-23 | | 14=3x-x-10 | | 7-p=4 | | 90*23=x | | 60=0.5x+32 | | 7/x-5=6 | | (b+3)(b^2+2b+1)=0 | | 5y^2+10y-48=0 | | 24+0.79=1.19x | | 9=4(-3)-3 | | -14(-10x-13)=1162 | | -24+7x=25 | | 2x22/7x25x3.5 | | 4x^6+11x^5-x^3+7x+7=0 | | 3x-6(6x+31)=12 | | 2*x=512 | | 1/10_=k/100 | | 3x-4+9x=10 | | 2x+y^2=36 | | (x+9)+(4x^2)=0 | | 5x+1=8x-32 | | 5/9x31/90 | | (f+g)(x)=(x+9)+(4x^2) | | 20+5x=10-8x | | 11.5=14t+20.6 | | 21x+3y=210 | | x^2=-192 | | 30x^3+26x^2+4x= | | x-1/3=12 | | 6x+3x=3x-x | | x/2-3-x≥1 |

Equations solver categories